Characterization and determinants of organizational satisfaction in mexican workers of SMES - Mirón Juárez, Carlos Alberto; García Hernández, Claudia; Félix Verduzco, Rafael Octavio; Ochoa Ávila, Eneida (Cuadernos de Administración, 2020)
This study aimed to build a model that allows us to understand organizational satisfaction from variables related to job satisfaction; Likewise, we proceeded to validate and confirm the dimensions of a scale to measure satisfaction with the organization within the work environment based on the proposal by Cayama and Pazmiño (1998), in addition to characterizing organizational satisfaction in a sample of 646 employees, both sexes between 18 and 70 years, workers of small and medium enterprises (SMEs). From the Rasch analysis, relevant psychometric values were observed, identifying seven items as alien to the satisfaction dimension; An explanatory model was obtained that showed relevant adjustment criteria, observing that the main predictors of satisfaction with the organization were satisfaction with supervision (β = .84) and salary satisfaction (β = .75). Likewise, it was observed that the type of position, the marital status, the type of contract and the number of children had a significant impact on the differences in satisfaction. New studies are suggested that regain satisfaction with the organization as a relevant construct for a specific analysis of labor relations, as well as the extension of the sample to other types of workers and greater age ranges and seniority.